2008
DOI: 10.1038/ijo.2008.126
|View full text |Cite
|
Sign up to set email alerts
|

Selective reduction in body fat mass and plasma leptin induced by angiotensin-converting enzyme inhibition in rats

Abstract: Objective: There is emerging evidence that angiotensin stimulates adipocyte differentiation and lipogenesis. This study tested the hypothesis that inhibition of angiotensin II by treatment with an angiotensin-converting enzyme inhibitor, perindopril, would reduce fat mass in rats. Design: After a 12-day baseline, rats were divided into two groups: one was untreated and the other received perindopril (1.2 mg kg À1 per day) in drinking water for 26 days. Subjects: In total, 16 male Sprague-Dawley rats aged 10 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 51 publications
3
32
1
Order By: Relevance
“…Among previous studies that reported decreased body weight/body fat with an antagonist of the RAS, several reported decreased food intake 41,42 whereas others did not. 22,43 Therefore, the role of decreased food intake is still to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Among previous studies that reported decreased body weight/body fat with an antagonist of the RAS, several reported decreased food intake 41,42 whereas others did not. 22,43 Therefore, the role of decreased food intake is still to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the relationship between circulating RAS activity and obesity is likely bi-directional. The RAS contributes to energy balance, as genetic [10][11][12][13] and pharmacological [14][15][16][17][18] inhibition of the RAS in rodent models generally results in a negative energy balance (lean animals and/or resistance to weight gain), and chronic elevations in plasma renin activity can lead to obesity [19].…”
Section: Introduction the Ras And Obesitymentioning
confidence: 99%
“…In week 11, body composition was determined in rats fed a HFD (n = 9) and control diet (n = 4) by dual energy X-ray absorptiometry as previously described [40]. At the conclusion of week 12, individual body weights were recorded for each animal.…”
Section: Body Composition and Tissue Collectionmentioning
confidence: 99%